In the Mouth of the Wolf: Cancer and Its Contingencies - Gore, Steven (Ars Medica, 2015)
We feel his ivory teeth, we feel his head shake, we feel his warm drool and the rhythmic trot of his lean legs and padded feet. We smell gamey breath blowing from his wet nose and through his teeth, and we breathe musty dust rising from the trail ...